Supporting learning recovery in elementary schools through student participation in Kampus Mengajar Perintis program - Rahmawati, Rahmawati; Dewi, Pajriani; Usnaini, Neni; Astuti, Fuji (Journal of Modern Education Research, 2026)
This study aims to describe the conditions and problems occurring in schools, as well as the solutions implemented by university students during the Kampus Mengajar Perintis. To achieve this objective, this study employed a qualitative descriptive method using observation and documentation techniques. The research subjects comprised nine Grade III students at SD N Cidokom 03. The study was conducted from 12 October to 18 December 2020 at SD N Cidokom 03, Rumpin District, Bogor Regency. The research data consisted of observational findings and supporting literature. The results indicate that the university students participating in the Kampus Mengajar Perintis programme at SD N Cidokom 03 focused primarily on strengthening literacy and numeracy learning, as well as cultivating character values through traditional games and other simple activities. In addition, the students assisted teachers throughout teaching and learning activities, including instruction delivery and administrative tasks.